Simultaneous Estimation of Rosuvastatin Calcium and Fenofibrate in Bulk and in Tablet Dosage Form by UV-Spectrophotometry and RP-HPLC (Stamford Journal of Pharmaceutical Sciences, 2011)
Two methods are described for the simultaneous estimation of Rosuvastatin Calcium and Fenofibrate in binary mixture. The first method was based on UV Spectrophotometric determination of two drugs, using simultaneous equation method. It involves absorbance measurement at 243nm (λmax of Rosuvastatin Calcium) and 287nm (λmax of Fenofibrate) in methanol; linearity was obtained in the range of 1-6 μg/ml and 4-28 μg/ml for Rosuvastatin Calcium and Fenofibrate, respectively. The second method was based on HPLC separation of two drugs in reverse phase mode using Luna C18 column. Linearity was obtained in the concentration of 1-7 μg/ml and 4-28 μg/ml for Rosuvastatin Calcium and Fenofibrate, respectively. Both these methods have been successively applied to pharmaceutical formulation and were validated according to ICH guidelines.   Key words: Rosuvastatin Calcium; Fenofibrate; UV Spectrophotometry; HPLC; Method validation DOI: http://dx.doi.org/10.3329/sjps.v4i1.8868 SJPS 2011; 4(1): 58-63